Myositis ossificans of the medial pterygoid muscle post dentigerous cyst enucleation: case report - Jiménez Zúñiga, Fidel (2020)
Myositis ossificans is a rare entity characterized by heterotopic bone deposition in soft tissues, being located mainly in muscle, two variants have been described: progressive myositis ossificans (PMO) and traumatic myositis ossificans (TMO). The objective of this article is to report the first case of TOM diagnosed in Mexico, in an 11-year-old female patient, after enucleation of the dentigerous cyst, developed progressive limitation to the oral opening, pain and trismus, to the physical examination without palpation of mass or deformities within the cavity, with an oral opening of 0 mm; The tomographic and reconstruction study identified a well-defined hyperdense image compatible with calcification at the level of the medial pterygoid muscle. The lesion was resected, confirming the diagnosis by histopathology. Nowadays the patient currently clinical surveillance and physical therapy support, with no recurrence.